Senescence, NK cells, and cancer: navigating the crossroads of aging and disease - Gergues, Marina; Bari, Rafijul; Koppisetti, Sharmila; Gosiewska, Anna; Kang, Lin; Hariri, Robert J. (Frontiers in Immunology, 2025)
Cellular senescence, a state of stable cell cycle arrest, acts as a double-edged sword in cancer biology. In young organisms, it acts as a barrier against tumorigenesis, but in the aging population, it may facilitate tumor growth and metastasis through the senescence-associated secretory phenotype (SASP). Natural killer (NK) cells play a critical role in the immune system, particularly in the surveillance, targeting, and elimination of malignant and senescent cells. However, age-related immunosenescence is characterized by declining NK cell function resulting in diminished ability to fight infection, eliminate senescent cells and suppress tumor development. This implies that preserving or augmenting NK cell function may be central to defense against age-related degenerative and malignant diseases. This review explores the underlying mechanisms behind these interactions, focusing on how aging influences the battle between the immune system and cancer, the implications of senescent NK cells in disease progression, and the potential of adoptive NK cell therapy as a countermeasure to these age-related immunological challenges.